Sorption and stability of trace elements on aluminum-substituted iron oxides - Cardoso, Daniel Kroehling Rodrigues (2023)
The trace elements arsenic (As), antimony (Sb), lead (Pb), and cadmium (Cd) are present in orogenic gold deposits positively correlated with gold. Others, such as the rare earth elements lanthanum (La) and ytterbium (Yb), do not present correlation with gold. The weathering of these rocks, intensified by mining activity, leads to a redistribution throughout the local drainage basin. Iron oxides precipitating from weathering products immobilize part of these elements. High contents of gold in secondary deposits attract artisanal mining (garimpo), which historically contaminates watercourses with mercury (Hg). In this study, iron oxides were precipitated from a solution containing As, Pb, Sb, Cd, La, Yb, and Hg in the presence and in the absence of aluminum (Al). The stability of the coprecipitates was evaluated through BCR and SBET extraction procedures. Most of the initial content of As, Pb, Yb, and Sb was coprecipitated with Fe-oxides in only two hours, while Cd and La persisted longer in solution. Aluminum isomorphic substitution in Fe-oxides favored La and Yb immobilization in the short- term, but favored As and Cd immobilization in the long-term. Goethite with Al substitution (Al-goethite) was the only phase identified in treatments with Al, and lepidocrocite precipitation was favored at high concentrations of trace elements. Arsenic and Cd were more stable coprecipitated with Al-goethite. On the other hand, La and Yb were more stable with Al- free-goethite or lepidocrocite. The extraction percentages of As, Cd and Sb from precipitates were lower than Pb, La and Yb, which might be related to higher incorporation of As, Cd and Sb into the oxides structure. The precipitates had high bioaccessible contents of As and, therefore, higher risk to oral exposure for children (HQ > 1). Mercury did not interfere with other elements sorption or stability, therefore the hypothesis that garimpo can remobilize other elements through desorption from Fe-oxides due to Hg introduction was not confirmed. The results were useful for enhancing comprehension of interactions between iron oxides and trace elements in natural systems, including aspects such as sorption mechanisms, stability, bioavailability, and toxicity. Keywords: Coprecipitation. Acid mine drainage. Garimpo. Arsenic. Goethite.